Peningkatan Proses Pembelajaran Dengan Model Quantum Teaching di Kelas V SD - Yolanda, Nadya; Reinita, Reinita; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
This study aims to describe the improvement of integrated thematic learning process using the Quantum Teaching model in class V of SD N 16 Koto Baru Solok. Subjects in the study were 22 teachers and students. Place of research in SD N 16 Koto Baru Solok. The results showed an increase in: a) RPP meeting I cycle 1 gained an average of 80.05% (sufficient), meeting I cycle 2 88.88% (good), increased in the second cycle to 97.22% (very good) ), b) The implementation of teacher activities in the first cycle of meeting 1 obtained 77.77% (sufficient), the first cycle of meeting 2 gained 86.11%, increased in the second cycle to 94.44% (very good), c) Implementation of cycle student activities I meeting 1 received 77.77% (enough), the first cycle of meeting 2 gained 86.11%, increased in the second cycle to 94.44% (very good), d) Assessment of student learning outcomes in the first cycle of meeting 1 received an average average 65,8, the first cycle of meeting 2 obtained an average of 78,5, increasing in the second cycle to 94.Keyword : Quantum Teaching, integrated thematic